Marine Mammals in Syria - Saad, Adib Ali (2020)
The Syrian marine water is one of the least studied areas for cetaceans in the Mediterranean Sea. Lack of basic knowledge, such as species composition and habitat, makes it impossible to develop effective conservation measures. The survey carried out along the Syrian coast by monitoring the stranding individuals on the shore since 2002 showed that there were 11 species of marine mammals living in/or visiting the Syrian marine waters at present of which 10 species belonging to the cetacean order and on belonging to pinnipeds order. The following species have been recorded: Pseudorca crassidens, Megaptera novaeangliae, Physeter macrocephalus, Tursiops truncatus, Stenella coeruleoalba, Delphinus delphis, Ziphius cavirostris, Grampus griseus, Balaenoptera physalus, Balaenoptera acutorostrata, and Manchus manchus. On the other hand, there are four species whose presence in the Syrian marine waters was mentioned a century ago by the researcher Gruvel and his team during three missions (1929‚Äì1931), but neither alive nor dead have been seen in this area during the surveys that were carried out since 1996 until the present, these species are: Phocoena phocoena, Globicephalus melas, Phocoena communis, Hyperoodon rostratus, Balaenoptera musculus. These observations reflect the vulnerability of marine mammals to anthropogenic activities, such as fishing operations, shipping, seismic activities, and climate change.